2010
DOI: 10.1186/1472-6963-10-94
|View full text |Cite
|
Sign up to set email alerts
|

Four minutes for a patient, twenty seconds for a relative - an observational study at a university hospital

Abstract: BackgroundIn the modern hospital environment, increasing possibilities in medical examination techniques and increasing documentation tasks claim the physicians' energy and encroach on their time spent with patients. This study aimed to investigate how much time physicians at hospital wards spend on communication with patients and their families and how much time they spend on other specific work tasks.MethodsA non-participatory, observational study was conducted in thirty-six wards at the University Medical C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 23 publications
1
33
1
8
Order By: Relevance
“…We found that female patients with companions had longer consultations (7.7' vs. 6.4'); this figure is greater than that which has been reported for the hospital setting (4 minutes and 17 seconds for each patient on the ward and 20 seconds for his or her relatives) [36] (Figure 2), but less than the communicated by other authors in general medicine (10-12 minutes) [37], and it may be interpreted that longer consultations are associated with more adequate diagnoses, at least in psychological problems [38], although in our study the content of the interview was not collected (Table 3). …”
Section: Duration Of the Consultationcontrasting
confidence: 76%
“…We found that female patients with companions had longer consultations (7.7' vs. 6.4'); this figure is greater than that which has been reported for the hospital setting (4 minutes and 17 seconds for each patient on the ward and 20 seconds for his or her relatives) [36] (Figure 2), but less than the communicated by other authors in general medicine (10-12 minutes) [37], and it may be interpreted that longer consultations are associated with more adequate diagnoses, at least in psychological problems [38], although in our study the content of the interview was not collected (Table 3). …”
Section: Duration Of the Consultationcontrasting
confidence: 76%
“…[1][2][3]5,6 Similarly, we found that physicians spent 5.3 minutes per patient-about 13% of an 8-hour shift. We also found that communication times varied substantially by provider, from a mean of 2 minutes per patient to greater than 12 minutes per patient.…”
Section: Discussionsupporting
confidence: 54%
“…Studies conducted at single institutions in the US [1][2][3] and elsewhere [4][5][6] have found that hospitalists generally spend little time communicating with their patients, and that there is often disagreement between doctors and both nurses and patients about the plan of care. 7,8 However, it is not known how much time physicians actually spend communicating with nurses and other physicians, and more importantly, whether more time spent communicating is associated with higher levels of agreement regarding the plan of care or greater patient satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Although we reported previously that HCPs felt that procedures with short verbal information were feasible [14], it remains a topic of debate whether HCPs that were not part of this trial feel the same way, since it is well known that HCPs suffer from time constraints, and can thus spend less time informing patients about e.g. their treatment [20,21].…”
Section: Doi: 101159/000492662mentioning
confidence: 92%